2013
DOI: 10.1155/2013/324864
|View full text |Cite
|
Sign up to set email alerts
|

Neonauclea reticulata(Havil.) Merr Stimulates Skin Regeneration after UVB Exposure via ROS Scavenging and Modulation of the MAPK/MMPs/Collagen Pathway

Abstract: In this study, we investigated whether the protective effects of Neonauclea reticulata water extract against ultraviolet B (UVB) irradiation in human skin fibroblast cell cultures (Hs68) are governed by its ability to protect against oxidative stress and expression of matrix metalloproteinases (MMPs). We found that Neonauclea reticulata extract exhibited DPPH scavenging activity and inhibited AAPH-induced haemolysis of erythrocytes in a dose- and time-dependent manner. We also found that pretreatment of fibrob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
56
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 26 publications
0
56
0
1
Order By: Relevance
“…Both the TBARS and SOD levels may be used as markers of oxidative stress. Most products and vitamin-based treatments used to prevent skin aging involve antioxidation properties [27][28][29]. In this study, the data suggest that overexposure to UVB irradiation leads to increased TBARS level and decreased SOD level, resulting in significant skin damage.…”
Section: Discussionmentioning
confidence: 68%
“…Both the TBARS and SOD levels may be used as markers of oxidative stress. Most products and vitamin-based treatments used to prevent skin aging involve antioxidation properties [27][28][29]. In this study, the data suggest that overexposure to UVB irradiation leads to increased TBARS level and decreased SOD level, resulting in significant skin damage.…”
Section: Discussionmentioning
confidence: 68%
“…Our data showed that the number of hyperacetylated genes was three times larger than that of hypoacetylated genes, which was consistent with the result of global histone H3 acetylation. Furthermore, cluster analysis results of the ChIP‐chip data showed that the genes identified as hyperacetylated belonged to several different ontological domains, such as collagen catabolic processes and regulation of small GTPase‐mediated signal transduction, which are critical factors in skin photoageing …”
Section: Discussionmentioning
confidence: 99%
“…UV irradiation has been reported to induce expression of MMP‐1, MMP‐3 and MMP‐9 in human skin or dermal fibroblasts . Part of the reason is that UV irradiation can activate the GTPase–mitogen‐activated protein kinase pathways including JNK, p38 and extracellular signal‐related kinase (ERK); then the synergistic action of JNK, p38 and ERK results in activator protein‐1 activation with subsequent enhanced expression and activation of different MMPs …”
Section: Discussionmentioning
confidence: 99%
“…UV irradiation increases collagenase activity and reduces the production of collagen, resulting in wrinkle formation through the degradation of collagen in the dermal extracellular matrix (16). Exposure to UV light produces free radicals, releasing pro-inflammatory cytokines and growth factors, which activate proteases that degrade collagen elastin (17).…”
Section: Discussionmentioning
confidence: 99%